2010
DOI: 10.1097/mbc.0b013e32832f2b08
|View full text |Cite
|
Sign up to set email alerts
|

Unusual onset of venous thromboembolism and heparin-induced thrombocytopenia in a patient with essential thrombocythemia

Abstract: Essential thrombocythemia is a hematological disorder characterized by clonal hemopoiesis in the bone marrow and increased number of circulating platelets. It is usually discovered accidentally at the time of routine blood examinations or can become clinically evident with either thrombotic or hemorrhagic complications. In the present article, we describe the case of a 66-year-old woman with pneumonia due to Pneumocystis carinii, who experienced deep vein thrombosis and pulmonary embolism during hospitalizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Anecdotal data on relationship between HIT and MPNs are reported [26], but few studies have systematically approached the problem. [27][25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anecdotal data on relationship between HIT and MPNs are reported [26], but few studies have systematically approached the problem. [27][25].…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the observed risk of HIT is higher in patients with MPNs. [24] [25][26][27]. The aim of our study is to evaluate the occurrence of new thrombotic events among patients with ET with JAK2 V617F mutation treated with un-fractioned (UFH) or low molecular weight heparin (LMWH).…”
Section: Introductionmentioning
confidence: 99%
“…ET can be asymptomatic, and bone marrow biopsy as workup for thrombocytopenia (HIT) can reveal an unusual combination of ET and HIT [ 12 ]. To avoid the delay in diagnosis and its attendant complication, delta change in platelet count rather than the absolute value should be considered and evaluated whilst considering the diagnosis of HIT in the setting of ET [ 13 ].…”
Section: Discussionmentioning
confidence: 99%